Analysis of the Judge's Decision in Determining Custody Rights of Minors After Divorce: Study of Decision Number 708/Pdt.G/2025/PA.Skh at the Sukoharjo Religious Court - Muhammad Fajrul Minan; Baehaqi Baehaqi; Salman Salman; Aditya Fajri Kurnia Pradana; Muhammad Kurniawan Budi Wibowo; Jeong Chun Phuoc (Al-Hiwalah: Journal of Sharia Economic Law, 2026)
This study aims to analyze in-depth the judge's juridical considerations in granting custody of a minor child to the biological father in Decision Number 708/Pdt.G/2025/PA.Skh. The primary focus is to evaluate the consistency of the decision with the principle of "the best interest of the child" and to examine the extent to which the judge's arguments override maternal preference as normatively regulated in Article 105 of the Compilation of Islamic Law. The analysis is conducted to ensure legal certainty and the protection of children's human rights within the context of divorce. The methodology employed in this study is normative juridical with a case study and statutory approach. The data sources consist of secondary legal materials, including primary legal materials such as the Marriage Law, the Child Protection Law, the Compilation of Islamic Law, and Decision Number 708/Pdt.G/2025/PA.Skh. Data collection techniques were conducted through literature review and documentation, analyzed qualitatively using an interactive model. This approach enables the researcher to systematically deconstruct trial facts and the legal construction established by the panel of judges. The results indicate that granting custody to the father was based on evidentiary facts regarding the mother’s negligence in caregiving and her absence from the proceedings (verstek), which reinforced the petitioner's claims concerning her moral and psychological incapacity. The study concludes that the "best interest of the child" principle serves as a legal instrument capable of overriding the maternal preference in Article 105 of the Compilation of Islamic Law when there is a proven threat to the child's developmental stability. Recommendations include the urgent need for standardized parenting eligibility parameters within Supreme Court regulations and the optimized involvement of psychological experts to ensure the sustainable psychosocial well-being of the child.